Research on the Digital Level Calculation and Construction Path of Fishery Under the Background of “Blue Granary” Strategy - LIU Dan; CHEN Qiuying; MA Naiyi (Haiyang Kaifa yu guanli)
Integrating digital technology into fishery development is beneficial for enhancing the quality and efficiency of the industry, achieving the goal of building “blue granary” with high quality, ensuring food security, and driving modernization of agriculture and rural areas. Firstly, through a network relationship map, a keyword analysis was conducted on the 14th Five-Year Plan (2021—2025) for National Economic and Social Development and the Long-Range Objectives Through the Year 2035 for various provinces, autonomous regions and centrally administered municipalities, as well as the 14th Five-Year Plan for National Fisheries Development Plan. It was found China’s digitalization in fisheries is quite significant. Secondly, an entropy method was used to calculate the comprehensive value of digitalization level in fisheries across different provinces and cities in China. It was discovered the overall level of digitalization in fisheries in China is relatively low, with only Shandong Province having a score above 80. The development of digitalization in fisheries shows slow growth with fluctuations. Moreover, there is a large disparity in digitalization levels among different provinces and cities, resulting in uneven development. Additionally, using the DEA-BCC model further evaluated the impact of innovation and promotion efficiency of fisheries science and technology on the development momentum of digitalization level in fisheries. It was found there are significant differences in efficiency, stability, and input-output optimization among different regions. Finally, three constructive paths were proposed: (1) consolidating the hardware and software facilities for digitalization in fisheries to enhance the overall level of digitalization; (2) improving the efficiency of fisheries science, technology, and promotion to boost the development momentum of digitalization level in fisheries; (3) reshaping the relationships between the industrial chain, supply chain, enterprise chain, spatial chain, and value chain in fisheries with digitalization as the core. By utilizing digitalization level in fisheries, it is possible to achieve precise control over key areas and critical processes in fisheries, thereby promoting the realization of the strategic goal of building “blue granary.”